Meningkatkan Kemampuan Analisis Kalimat Persuasif dalam Teks Pidato Melalui Model Pembelajaran TGT (Teams Game Tournament) pada Kelas VIII G SMPN 50 Kota Batam - Dinda Nur Dwi; Delia Fitri; Khairun Nisa; Nur Melisa Putri; Tere D’amor Philip; Etik Triwahyuni; Fabio Testy Ariance Loren (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the significant effect of the TGT (Team Game Tournament) learning model on class VIII G at SMP Negeri 50 Batam and the comparison with the lecture method applied in class VIII C on student learning outcomes regarding Persuasive Sentence Analysis in Speech Texts. In this study, the author used a quasi-experimental design approach and applied a pretest and posttest. The research population was taken from 3 classes in class VIII SMP and the class research sample taken was in class VIII G which consisted of 29 students as the experimental class, then class VIII C which consisted of 29 students became the control class. The data analysis technique first carried out a swimmer test which required a normality test and a homogeneity test, then after the normal and homogeneous data were known, it was continued with a hypothesis test (t-test).